Validation of the menopause representation questionnaire (MenoSentations-Q) among Iranian women and cross-cultural comparison with Portuguese women - Zahra Arab Borzu; Mahmood Karimy; Mafalda Leitão; Filipa Pimenta; Rita Albergaria; Zahedeh Khoshnazar; Parisa Hosseini Koukamari (BMC Women's Health)
Abstract Background Menopause represents a critical stage in middle. Examining menopausal symptoms within healthcare system requires reliable and valid instruments. The Menopause Representations Questionnaire (Menosentations-Q) is a self-report scale grounded in Leventhal's self-regulation model. This study aimed to explore the psychometric properties of this questionnaire among Iranian women. Methods This study was conducted with women visiting healthcare centers in Saveh, Markazi province, Iran. A total of 320 eligible Iranian women and 354 Portuguese women (aged 45–65) completed the questionnaire. Structural validity was assessed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Internal consistency was evaluated through Cronbach’s alpha and McDonald’s omega. Convergent and divergent validity were determined using average shared variance, maximum shared variance, construct reliability, and Fornell and Larcker’s method. Cross-cultural validity was performed by multigroup CFA to assess invariance between two culturally distinct samples (Iranian and Portuguese). Results The Content Validity Ratio (CVR) and Content Validity Index (CVI) were 0.96 and 0.98, respectively, indicating strong content and face validity. EFA of 22 items revealed four factors-identity, positive and negative consequences, and control/awareness/cause factors, accounting for 61.29% of the total variance. CFA indicated good model fit (CFI = 0.96, TLI = 0.95, χ2/df = 1.74, GFI = 0.91, AGFI = 0.89, RMSEA = 0.04). Cronbach’s alpha (0.90) and McDonald’s omega (0.92) indicated good internal consistency. Convergent and discriminant validity values of MenoSentations-Q were also acceptable. Also, the instrument showed invariance between the two cultural groups. Conclusions The Persian adaptation of MenoSentations-Q demonstrated strong validity and reliability. Furthermore, the comparable responses between Portuguese and Iranian participants suggest shared representations of menopause across these cultures. Given the significance of menopause, tailored educational programs and interventions are essential to address potential challenges during this life stage. Employing standardized tools such as the Menopsentations-Q can support the development of effective strategies, including educational initiatives, support programs, and targeted interventions, to empower women and enhance their well-being during this transitional phase.